(3GdbQGAI GdSQjYI aj eLGd GdCYeGd (B/s - (3ehjOd, SJjas; (3ecJHI LQjQ (B( (3GdQjGV (B)s ((3GdQjGV (B:s (3ecJHI LQjQ ,s, 2001)
(3jJfGhd GdcJGH WQb dJMSjf hSQYI GdbQGAI(B.s
Keywords: (3GdbQGAIs; (3EOGQI GdCYeGds; (3GdfLGM GdEOGQjs